Strategies for Alleviating Poverty Through The Zakat, Infaq, and Shadaqah Collection and Management Program at Lazisnu Nganjuk - Hidayat, Ahmad Agus; Hakim, Fajrul; Al Farabi, Fahmi Akhyar (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
The aim of this research is to understand the strategy of collecting almsgiving funds through the coin movement program at Lazisnu Nganjuk and its management for poverty alleviation. The method employed is qualitative descriptive, with data collection techniques involving observation, interviews, and documentation, followed by analysis using SWOT and triangulation. In this study, it was found that the Coin Movement Program conducted by LAZISNU Nganjuk is implemented through the Direct Fundraising method, involving visiting donors at their houses, and actively involving them in the fundraising process. Additionally, the researcher found that the management of the proceeds from the coin program is not entirely managed by LAZISNU Nganjuk. Instead, the obtained funds are distributed to various sectors, including 5% managed by the Nahdlatul Ulama Branch Board (PC), 10% managed by the Lazisnu Branch Board (PC), 15% managed by the Coin Movement at the Sub-District Level (MWC), and 70% managed at the Village Level. Furthermore, the results of managing the Coin Movement are channeled through the fields of Education, Social Economy, and Disaster Response. Undoubtedly, the impact of this program will provide solutions to alleviate poverty in the community, especially in Nganjuk region. Keywords: Collection; Management; Coin movement and poverty program